(untitled) (University Heart Journal, 2011)
A 59 years old gentleman with hypertension, type-2 DM, dyslipidemia and atheroschlerotic stenosing coronary artery disease had the rare blood group Oh ((Bombay phenotype). After prophylactic conservation of two units of predeposit autologous blood, myocardial revascularization was successfully accomplished with off pump coronary artery bypass surgery (OPCAB). Postoperative recovery was uneventful. Key words: Bombay phenotype; OPCAB DOI: 10.3329/uhj.v6i2.7258 University Heart Journal Vol. 6, No. 2, July 2010 pp.110-113